THE IDEAS OF POLITICAL ETHICS OF SEYYED ALI KHAMENEI: AN ANALYSIS OF THE POLICIES OF AN ISLAMIC LEADER ON A NATIONAL AND INTERNATIONAL SCALE - Andi Novriansyah Saputra (ISSUE: Journal of Islamic Studies for Universal Dialogue, 2024)
The need for political ethics in national and international leadership is crucial to clarify the boundaries of political policy enforcement. Seyyed Ali Khamenei has demonstrated these ideas through his national speeches and political decisions as the Supreme Leader of the Islamic Republic of Iran. This study analyzes the political ethics of Seyyed Ali Khamenei using library research methods and a qualitative approach. It is descriptive-analytical in nature, extracting the core ideas of Seyyed Ali Khamenei from books that detail his life and articles from websites that compile his various speeches, formulating them into this academic work. The political ethics proposed by Seyyed Ali Khamenei focuses on two main themes: unity and justice. Regarding unity, Ali Khamenei views it as a necessity, even a principle that must be steadfastly upheld by the entire Muslim community. Concerning the theme of justice, Seyyed Ali Khamenei implements the concept of wilāyat, which is expected to foster love, and equality, and uphold justice for every citizen. According to him, an effective government strengthens the relationship between the leader and the people, and a progressive nation achieves peace and justice for humanity.